“My safe haven turned into a terror zone”: A qualitative study of family members’ experiences of violence by brain tumor patients - Amina Guenna Holmgren; Annika Malmström; Eskil Degsell; Johanna Simmons; Lisa Kastbom (PLoS ONE, 2026)
Background Knowledge is lacking regarding how the experience of being exposed to violence is affected when the perpetrator suffers from behavioral and personality changes (BPC) due to a brain tumor. This study is part of the Swedish national research project BRAVE - B rain Tumor R elated A ggression and V iolence E xposure . The aim was to explore experiences of family members exposed to violence by a person suffering from BPC associated with a brain tumor. Methods Individual interviews were conducted with 25 family members who have been exposed to violence by patients with primary brain tumor. The interviews were analyzed using qualitative content analysis. Results The participants reported various forms of violence and expressed intense suffering, loneliness and social isolation. The homes sometimes shifted from being a safe place to being a place marked by fear and unpredictability. In adapting to violence, what initially seemed unreasonable, gradually became “the new normal”. Different strategies to minimize risks and damage were described. Self-blame and shame were often associated with an inability to love the patient “in sickness and in health”, despite the violent actions by the patient. When the death of the perpetrator was viewed as the only means of escape, participants also expressed feelings of guilt and shame. Conclusions Our study highlights extensive suffering, vulnerability, loneliness and isolation among family members exposed to violence by brain tumor patients. An intervention that provides appropriate support for brain tumor patients, family members and staff who encounter them is urgently needed.